555 The Unintended Consequences Of COVID-19 on the Quality of Documentation of Operation-Notes. (4th May 2021) - Camilleri-Brennan, J; Lim, M
Abstract: Introduction: Operation-notes are crucial as they impact on the care of patients post-operatively. During COVID-19, a sizeable proportion of General Surgical procedures were performed at a local "cold" site private hospital. This study aims to determine the direct impact of COVID-19 on the standard of operation-note documentation at a non-routine site compared to our routine site. Method: The Royal College of Surgeons Good Surgical Practice guidance highlights 19 key-variables to record within operation-notes. 300 consecutive operations were identified between May and August 2020 and details of electronic operation-notes collected. Throughout this study period, educational emails and posters were introduced at both sites secondary to ongoing audit. Results: 228/300 (76%) operations took place at our main hospital. The remainder were commissioned to the other. Operating surgeons and anaesthetists were similar at both sites. Quality of documentation was poorer for many key variables at the cold site when compared with the main site (operating-surgeons (22% vs 91%), urgency of operation (62% vs 99%), antibiotic prophylaxis (72% vs 99%) and DVT prophylaxis (21% vs 98%)). Conclusions: COVID-19 has resulted in many unintended consequences including a reduction in the quality of operation-notes. Moving forward, this may be reduced by improving information technology resources and increasing awareness and education.